Study of Extraction Calophyllum inophyllum L using Microwave Hydrodiffusion Gravity And Chemical Extraction method - Raka Selaksa Charisma Muchammad; Mahfud Mahfud; Lailatul Qadariyah (IPTEK The Journal for Technology and Science, 2020)
In this study, the oil extraction of Calophyllum inophyllum L using microwave hydro-diffusion gravity method and chemical extraction method were elaborated. The Microwave Hydrodiffusion Gravity (MHG) method is a new green technique which combines microwave-assisted technology and gravitation. It is used to produce oil yield faster and at a low cost. In comparison, a chemical extraction method is a conventional method. The raw material pretreatment, extraction time, microwave power, and the material size have become a crucial factor of extraction. In general, the MHG method yields a higher yield than the chemical extraction method. The MHG method is simple and less solvent. It requires faster extraction time and produces higher oil yield.